If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6x + -3x = 36 Combine like terms: 6x + -3x = 3x 9 + 3x = 36 Solving 9 + 3x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 36 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 36 + -9 3x = 36 + -9 Combine like terms: 36 + -9 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| 2x+2=96 | | 13=1-2x-2x | | 4x-3-2x=-3 | | 26=3c-3(6-2c) | | Vf=vi+(9.81)6 | | 4x-5=-19 | | 7x+1-2x=41 | | 2x^2-4x+6y-10=0 | | -27+6d=7(4d+8) | | 8+4x-3x=-2 | | 13x-31+8x-176=180 | | rt-2n=fort | | 3x-4(x+3)=22 | | 2(y+5)=y+13 | | 23=4x-x-10 | | (10x^2)+3=11x | | -3(n-6)=12(n-4)+7n | | 12y-15y=584 | | 8(t-4)+7t=5(3t+4)-8 | | -3x-3-x=21 | | 3x-3+4x+8=75 | | -3k-7=-22 | | -3(n-6)=12(n-4)+7 | | 10b+14-4b=-7-b | | -3(5t-2)+7t=5t-6 | | .5=1x-2(1.3x-4) | | 1.7-2.1a+4.5a=-6.7 | | 3x^2+32x+20=0 | | -3(n-6)=13(n-4)+7 | | 4(2x+3y)+2(4-x-3y)+2= | | 2x+7y=17.50 | | X+x-17=155 |